Ancillary Care: From Theory to Practice in International Clinical Research. - Pratt, B; Zion, D; Lwin, K; Cheah, P; Nosten, F; Loff, B (2013)
How international research might contribute to justice in global health has not been substantively addressed by bioethics. This article describes how the provision of ancillary care can link international clinical research to the reduction of global health disparities. It identifies the ancillary care obligations supported by a theory of global justice, showing that Jennifer Ruger's health capability paradigm requires the delivery of ancillary care to trial participants for a limited subset of conditions that cause severe morbidity and mortality. Empirical research on the Shoklo Malaria Research Unit's (SMRU) vivax malaria treatment trial was then undertaken to demonstrate whether and how these obligations might be upheld in a resource-poor setting. Our findings show that fulfilment of the ancillary care obligations is feasible where there is commitment from chief investigators and funders and is strongly facilitated by SMRU's dual role as a research unit and medical non-governmental organization.